Effect of Graveliness on Peach Based Agri-Horti System in Doon Valley - Lal, H.; Samra, J. S.; Tewari, R. K. (Indian Journal of Agroforestry, 2020)
A study was conducted on different soil:gravel proportions to assess the performance of peach under blackgram-toria based Agri-Horti system in Doon Valley during 1995 to 2001 at Research Farm Selakui, Dehradun. Peach plants planted in mixture having 100:0 soil:gravel proportion exhibited better plant height, crown spread and trunk diameter, improved N, P, K, Ca and Mg contents of leaf and produced 77, 48 and 15 per cent more fruits of better quality than 20:80, 50:50 and 75:25 soil:gravel proportions, respectively under irrigated condition. Similarly, application of irrigation in peach trees exhibited better plant growth, improved nutritional status of leaf and increased fruit yield by 39 per cent over rainfed condition under 100:0 soil:gravel proportion. Blackgram-toria grown on 75% or more soil as rainfed gave better yield than other soil gravel proportions. Under drip irrigation system, peach tree planted on 75 or more per cent of soil and intercropped with blackgram-toria as rainfed proved more beneficial with highest net profit of more than Rs. 10,000 ha-1 year-1 with maximum benefitcost ratio of 1.65 than other soil:gravel proportions.